Influence of cross section geometry on the confinement of reinforced concrete columns with CFRP composites - Paula, Raquel F.; Silva, Manuel G.; Vinagre, João (My University, 2006)
Confinement effectiveness of externally bonded FRP jackets depends on different parameters namely type of concrete, steel reinforcement, FRP jacket stiffness (type of FRP, number of plies and design of wrap), shape of cross section, radius of corners for non-circular sections, and loading conditions. In order to investigate the effect of some of these parameters on the axial behavior of columns under compression and to quantify the level of confinement exerted on the concrete core, an experimental program has been developed. The experimental research consisted of a sequence of axial compressive tests on cylinders and square prisms. Prisms were divided into three representative groups: sharpedged sections and sections with rounded corners with corner radii equal to either 20mm or 38mm. The results presented in this paper are for the columns which were wrapped with two plies of unidirectional carbon fibers.
Comunicação apresentada em International Symposium Polymers in Concrete (ISPIC 2006), Guimarães, 2006